FEKUNDITAS CACING Pontoscolex corethrurus Fr.Mull.PADA MEDIA DENGAN PENAMBAHAN LIMBAH CAIR TAHU - Marlina, Septi; Indriati, Gustina; Lusi, Armein (STKIP PGRI Sumbar, 2013)
ABSTRACTEarthworm is a organism that give multifunction for human life and living organism in earth. It have the quality is heterotrof. The reproduction growth of eartworm that have the quality is hemaprodite biparental, it is earthworm that have two tool reproduction all at one in one part of body. Reproduction Pontoscolex corethrurus Fr.Mull worm it can be affected with any effect that have given to Pontoscolex corethrurus Fr. Mull with using tofu waste. Base of that have done the research with a goal for know the effects fecundity Postoscolex corethrurus Fr. Mull worm in media with increase of tofu waste. This research use complete random with five treatment and five repeated. The treatment that have given is the control with 0,1%, 0,2%, 0.3% dan 0,4% treatment. The data have analyted with use analysis od varians test if have difference continued with DNMRT test. This research have done in Zoology laboratorium Biology Departmen FMIPA Of Padang University state at Juli-August 2013. The result of analysis had foundthat amount cocoon Pontoscolex corethrurus Fr. Mull wormin A, B, C,D and E have difference of total average cocoon . In A treatment amount fourty cocoon is highest total cocoon from total other treatment this it real difference with other treatments but cocoon total in B, C, D dan E treatment not real difference. In conclusion, tofu waste can be fertility boosters and suitable with the dose requirement.